Homosexuality: Reserved Acceptance and Incomplete Social Change - Moitra, Moulinath (Journal of Advanced Research in Humanities and Social Sciences; Vol 8 No 3 (2021): Journal of Advanced Research in Humanities and Social Sciences, 2022)
In a time where a person’s social behaviour is greatly influenced by their relational social identity, gender is an integral factor in determining one’s self-concept. With the concept of heteronormativity being questioned and a movement towards a more gender-fluid and non-binary acceptance of gender, it is important to take cognizance of the inception of a shift where the lines bordering the concept of sexual orientation are blurred. As we move from the black and white to more grey areas in defining and differentiating between sex and gender, the avenues of research further increase with the widening of the ambit but in lieu of the purpose of this research, this paper will specifically tackle the issue of Homosexuality. The recent changes in legislations and laws prevailing in the country has brought this issue to the limelight as well as caused a lot of controversy. This paper aims to critically analyse and scrutinize the history of homosexuality in India from perusing the ancient Hindu texts which iterated the sexual lifestyle of individuals to inspecting modern laws currently in practice, all this to holistically determine how homosexuality became a taboo and is a source of scorn for those of orthodox and dogmatic ideologies. This paper also contains an empirical part where a survey was conducted to help the readers get acquainted with the mindset of a sample se of the population which in specific ways could represent the society as a whole. How to cite this article: Moitra M. Homosexuality: Reserved Acceptance and Incomplete Social Change. J Adv Res Humani Social Sci 2021; 8(3): 16-20.